Boycott! the academy and justice for Palestine - Maira, Sunaina 1969- (University of California Press, 2018)
"The Boycott, Divestment, and Sanctions movement (BDS) has expanded rapidly though controversially in the United States in the last five years. The academic boycott of Israeli academic institutions is a key component of that movement. What is this boycott? Why does it make sense? And why is this an American Studies issue? These key questions and others are answered in this short essential book. Boycott! situates the academic boycott in the broader history of boycotts in the United States as well as Palestine and shows how it has evolved into a transnational social movement that has spurred profound intellectual and political shifts. It explores the movement's implications for antiracist, feminist, queer, and academic labor organizing and examines the boycott in the context of debates about Palestine, Zionism, race, rights-based politics, academic freedom, decolonization, and neoliberal capitalism"...Provided by publisher
Includes bibliographical references
Keywords: Academic freedom -- United States; Boycotts -- United States -- 21st century; Academic freedom -- Palestine; Boycotts -- Palestine -- 21st century; Arab-Israeli conflict -- Social aspects